ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX PADA MATERI SPLDV BERDASARKAN TAHAPAN POLYA - Anida Nurul Fadilah; Haerudin Haerudin (IKIP Siliwangi, 2022)
The study aims to analyze the problem solving ability of junior high school students on linear equation system of two variable. The method of this study is qualitative descriptive method. The subject of this study is 20 students IX at one state junior high school in Kabupaten Karawang. Technique data collection using test and interviews. Technique data analysis using data reduction, data presentations and drawing conclusions. The results obtained in this study are from the 4 stages of mathematical problem solving ability, the percentages are as follows: (1) understanding the problem by 33%, (2) planning problem solving by 87%, (3) implementing a solution plan by 65%, (4) checked back by 47%. Most students with high abilities already understand the problems given, students with moderate abilities are mostly less careful in carrying out solving plans and students with low abilities mostly do not understand the problems contained in the questions.